A Cost‐Effective Management Practice to Decrease Phosphorus Loss from Dairy Farms. Issue 6 (1st November 2014) - McDowell, R. W.; Cosgrove, G. P.; Orchiston, T.; Chrystal, J.
Abstract : Phosphorus (P) loss from land can impair surface water quality. A paired‐catchment study was conducted on a grazed dairy farm that tested the hypothesis that cultivating and sowing a low‐P‐requiring grass in near stream areas and high‐P‐requiring clover ( Trifolium repens L.) elsewhere lost less P to water and was potentially more profitable than a mixed grass–clover pasture managed for the cover component. Two catchments were treated the same for 2 yr, after which 40% of the treatment catchment was cultivated around the stream, sown in ryegrass ( Lolium perenne L.) and fertilized with 150 kg nitrogen (N) ha −1 yr −1 and 10 kg P ha −1 yr −1 . White clover was established in the remainder of the catchment and received no N but 30 kg P ha −1 yr −1 . The control catchment received 150 kg N ha −1 yr −1 and 30 kg P ha −1 yr −1 . After the monocultures were installed, filterable reactive P and total P concentrations decreased by 44 and 26% respectively, while the better‐quality forage suggested a possible improvement in profitability. We concluded that with some caveats (e.g., a 2% increase in modeled N loss), using grass–clover monocultures strategically across a dairy farm may decrease P loss to surface water and improve profitability compared with a mixed pasture.